Parents' perception of family centred care for children hospitalized through road traffic accident: A qualitative study at two tertiary settings in Ghana - Lillian Akorfa Ohene; Kevin J. Power; Raghavan Raghu (Elsevier, 2019)
Background: Conceptually, Family Centred Care promotes better medical outcomes by ensuring that families play key supporting roles in children's adaptation to unfamiliar clinical environments. This care approach is crucial to minimising traumatic experiences resulting from Road Traffic Accidents and subsequent hospitalisations. Objectives: This study sought to understand Family Centred Care from a sub-Saharan context by exploring perceptions among parents and families whose children were hospitalised as a result of Road Traffic Accidents. Method: The study was conducted at two government-funded institutions located in Ghana's capital city - Accra. Pediatric surgical units which admit RTA injured children were purposively selected sites for data collection. Using Constructivist Grounded Theory approaches, 19 participants were interviewed. A semi-structured interview guide aided in-depth individual interviews with probing questions to elicit detailed information from participants. Data collection and analysis occurred iteratively. Here, we employed constant comparative methods. Broad categories and sub-categories emerged from the analysis. Findings: Significantly, all 19 participants embraced family centred care in principle. However, our observations revealed that both institutions practiced family centred care informally to a lesser degree. Three major categories emerged, namely: managing emotions, parental care roles and negotiating the system. Conclusion: Culturally, Ghanaians perceive parents' devotion to hospitalised children as synonymous with good parenting. Equally, emotional support and parents' negotiation powers are important prerequisites for greater participation in the care process. Hence, we recommend that a coherent national policy, robust clinical guidelines, and a culturally-sensitive Family Centred Care model are integral to parents' participation in hospitals in Ghana.